Kearifan Lokal Masyarakat dalam Pengelolaan Madu Tikung di Desa Ensabang Kecamatan Sepauk Kabupaten Sintang: Local Knowledge in The Management of Tikung Honey in Ensabang Village, Sepauk Sub-District, Sintang District - Pransiska, Desi Natalia; Kartikawati, Siti Masitoh; Muflihati (Forestry Faculty of Hasanuddin University, 2025)
Knowledge is essential for people to adapt to nature and becomes a cultural heritage in managing existing natural resources with knowledge, customary, and cultural norms in the community's concept of thinking. Forest honey from Ensabang Village, Sepauk District, Sintang Regency, is honey produced by Apis dorsata bees, which is managed by the community using the Tikung technique, the management of which is based on the community's local knowledge and customary rules. This research aims to examine forms of local knowledge in the management of Tikung honey. This research used interview techniques with all Tikung honey farmers, and the data was analyzed using qualitative descriptive analysis. The study results show that the management of Tikung honey is carried out individually. The Tikung is placed on the river bank and the ground, and the types of wood used to make Tikung are Tembesuk (Fagraea fragrans) and Kawi (Shorea balangeran). Harvesting forest honey is carried out at night, and packaging and marketing are carried out directly by honey farmers. The traditional rule is that people are prohibited from burning near nest trees, destroying and cutting down nest trees and food trees, and putting Tikung in other people's trees and gardens. There are written sanctions and fines for those who steal and claim other people's Tikung.